Does Antenatal Education Affect Level Of Empathy And Attachment Of Fathers? - POTUR, DİLEK; DEMİRCİ, NURDAN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Objective The study aimed to determine the effects of antenatal education on the paternal bonding and empathic tendency levels of men who would become fathers for the first time. Background There are a limited number of studies in the literature that have investigated the effects of antenatal education programmes on fathers. Methods This prospective, controlled quasi-experimental study was conducted in a hospital in Istanbul. The men in the antenatal educational group (EG) and their wives participated in training in antenatal classes. The men in the control group (CG) came for routine prenatal follow-up examinations with their wives. The Empathic Tendency and Paternal Postnatal Attachment Scales were used to collect the data. Results The Empathic Tendency Scale was applied before the education (1) - after the education (2) and at the 6th postpartum week (3), whilst the Paternal Postnatal Attachment Scale was used at the 6th postpartum month (4). EG had higher emphatic tendency levels in the 2nd and 3rd measurements and higher paternal bonding levels in the 4th measurement in comparison to CG (p < 0.05). Conclusion Antenatal education increased the emphatic tendency of the fathers and the effects of this education continued in the postpartum period and affected paternal bonding positively.
Keywords: Antenatal education; empathy; paternal bonding; PRENATAL ATTACHMENT; INFANT ATTACHMENT; DEPRESSION; INVOLVEMENT; CHILDBIRTH; PREGNANCY; CARE; EXPERIENCES; PREDICTORS; EFFICACY